Development Of DNA nanosensors as aptasensor for lysozyme and DNAzyme sensor for zinc ions - Wai, Jing Luen (2020)
DNA nanotechnology based on DNA aptamers and DNAzymes is highly beneficial because they provide more stable, programmable and manageable alternatives to their native counterparts (i.e. antibodies and enzymes) on top of being cost-effective.